Phylogenetic Analysis of Genes Responsible for the Primary and Secondary Response of Sinorhizobium meliloti Towards Salinity Stress - Muntyan, Victoria Spartakovna; Roumiantseva, Marina Lvovna (Research Advances and Challenges in Agricultural Sciences Vol. 6, 2024)
The nodule bacteria Sinorhizobium meliloti are mutualistic symbionts of alfalfa, which has a wide area of distribution, including the zone of arid agriculture, the soils of which are subject to salinization. S. meliloti, as typical saprophytes, are found in soils of different types and degree of salinity. Therefore, rhizobia must have a gene pool that determines their ability to adapt to different conditions. This paper presents the first results of phylogenetic analysis of genes involved in primary and secondary responses to the stress factor salinity. Analysis of 26 S. meliloti strains for which full genomic data are available showed that the pSymA replicon, on which the genes essential for symbiotic nitrogen-fixing activity are localized, also plays a significant role in the formation of the gene pool associated with tolerance to salinity stress. The identification of the closest putative phylogenetic relatives for all 14 genes studied allowed, for the first time, to gain insight into the evolutionary pathway of stress-related gene pool formation in nodule bacteria forming nitrogen-fixing symbiosis with leguminous plants.